2014
DOI: 10.1111/jsm.12624
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predicting Factors for Commonly Neglected Sexual Side Effects to Radical Prostatectomies: Results from a Cross-Sectional Questionnaire-Based Study

Abstract: Introduction Altered perception of orgasm, orgasm-associated pain, penile sensory changes, urinary incontinence (UI) during sexual activity, penile shortening (PS), and penile deformity following radical prostatectomy (RP) have received increasing attention from researchers. Aim The aim of this study is to describe the prevalence and predictors of the above-mentioned side effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 39 publications
4
87
0
Order By: Relevance
“…UI has been previously associated with the occurrence of climacturia after surgery [282930]. Indeed, in an assessment of the potential predictors of climacturia, Frey et al [30] showed a higher risk of climacturia in patients with postoperative UI, and similar findings were observed by O'Neil et al [29] in patients treated with surgery or radiation therapy.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomymentioning
confidence: 58%
See 2 more Smart Citations
“…UI has been previously associated with the occurrence of climacturia after surgery [282930]. Indeed, in an assessment of the potential predictors of climacturia, Frey et al [30] showed a higher risk of climacturia in patients with postoperative UI, and similar findings were observed by O'Neil et al [29] in patients treated with surgery or radiation therapy.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomymentioning
confidence: 58%
“…The exact prevalence of climacturia in patients who undergo RP is unknown, given the huge variability in reported rates, ranging between 20% and 93% (Table 1) [232425262728293031]. In 1996, Koeman et al [24] first assessed orgasmic problems in a small series of patients treated with RP and reported that 9 out of 14 patients experienced involuntary loss of urine at orgasm.…”
Section: Prevalence Of Orgasmic Dysfunctions After Radical Prostatectomymentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with peripheral neuropathy, sizing should be even more conservative. Further dissatisfaction is noted in patients with a risk factor for shortening such as those with Peyronie's disease [5] , post-radical prostatectomy [6] , post-neglected priapism [7] , and in patients with a concealed penis.…”
Section: Introductionmentioning
confidence: 99%
“…[345] Organ associated problems, urinary incontinence during sexual activity, penile sensory changes, penile shrinkage, and penile deformity are common side effects experienced by patient who had undergone radical prostatectomy and testicular cancer. [46]…”
Section: Introductionmentioning
confidence: 99%